Taxonomic revision of the microleafhopper genus Ziczacella Anufriev 1970 from Korea (Hemiptera: Cicadellidae: Typhlocybinae) - Hossain, Md. Shamim; Kwon, Jin Hyung (Zootaxa, 2019)
Four species of erythroneurine genus Ziczacella Anufriev, 1970 are revised. Among them, Ziczacella spinosa sp. nov. is new to science. Descriptions and illustrations of Korean species as well as a key and checklist of all known species are provided.